A Class of Special Solutions for the Ultradiscrete Painlevé II Equation - Isojima, Sh.; Satsuma, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
A class of special solutions are constructed in an intuitive way for the ultradiscrete analog of q-Painlevé II (q-PII) equation. The solutions are classified into four groups depending on the function-type and the system parameter.